Design and Validation of the Software for Strengthening Logical Mathematical Thinking (Logical Brain) - Silva Monsalve, Alexandra María; Bohórquez Ramírez, Gabriela (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The research was oriented towards the design and validation of the Logical Brain software. The proposed objective sought didactic and pedagogical strategies for the strengthening of logical mathematical thinking. A methodology for the implementation of educational software was addressed, which is composed of six phases and eleven sub-phases, integrating the design of an application made up of technical, pedagogical, and didactic dimensions. The evaluation and cataloguing form was used to evaluate the software, applied to teachers in the area of Technology and Education. The results show positive aspects in the evaluation of the software, identified by the participants in its validation.